Spontaneous remyelination following dimethyl sulfoxide-induced demyelination is accompanied by behavioral and neurological alteration in mice - Nikita V. Kudryashov; Alexander A. Gorbunov; Nadezhda B. Sviridkina; Sergey E. Mironov; Dmitriy A. Tikhonov; Andrey A. Nedorubov; Vladimir P. Fisenko (Belgorod National Research University, 2023)
Introduction: Dimethyl sulfoxide (DMSO) is a commonly used solvent that can be applied in experimental studies for preparation of hydrophobic solutions as well as in capacity of a cryopreservative in transplantology. According to modern data acquired from in vitro experiments, DMSO is able to change the structure of myelin by decreasing synthesis of its main components and inhibiting oligodendrocyte genesis. Aim of the study: We studied influence of DMSO on anxiety and compulsive-like behavior, pain perception, motor coordination and myelin quantity in the corpus callosum of the C57BL/6 mice brain after prolonged oral administration of the solvent and 4 weeks after administration was stopped. Materials and Methods: All the experiments were conducted on male inbreed C57BL/6 mice. DMSO was added to drinking water to achieve 0.01% concentration, and the obtained solution was administered ad libitum for 6 weeks. After 6 weeks of administration of DMSO and 4 weeks after administration of DMSO was stopped, anxiety-like behavior in open field test, compulsive-like behavior in marble burying test, motor coordination in rotarod test, pain perception in tail-immersion test, as well as myelin quantity in the corpus callosum were evaluated. Results: It was established that DMSO consumed for 6 weeks was associated with decrease in the myelin quantity in thecorpus callosum and thermal hyperalgesia in tail-immersion test. During 4-week period after DMSO administration was stopped, attenuation of demyelination was observed, followed by an increase in thermal hyperalgesia in tail-immersion test, as well as vertical locomotion and exploratory activity in open field test. Conclusions: 6-week ad libitum administration of 0.01% DMSO solution was associated with demyelination in corpus callosum of С57BL/6 mice, followed by thermal hyperalgesia. Cessation of DMSO led to spontaneous remyelination with an increase in thermal hyperalgesia, vertical locomotion and exploratory activity of mice.